The relationship beetwen strength, speed, flexibility, agility, and anaerobic power in elite athletes - Tatlisu, B.; Karakurt, S.; Agirbas, O.; Ucan, I. (International Journal of Applied Exercise Physiology, 2019)
The aim of this study was to determine whether there is a relationship between strength, speed, flexibility, agility, and anaerobic power in elite athletes. In various sport branches 29 active male athletes participated in this study with an average age of 21.14±1.98 years who without any health problems. Back and leg strength were measured by dynamometer (Takei), speed was measured by 20 meters test, agility was measured by T test, flexibility was measured by sit and reach test, vertical jump sit-reach test by Jumpmeter (Takei) anaerobic power was calculated by the Lewis formula. The data were analyzed in SPSS 22.0 for Windows package program. Bivariate - Pearson Correlation test was used to determine the relationship between strength, speed, flexibility, agility, and anaerobic power. The results were interpreted as .05 significance level. We were found positive and significant relationships between the back and leg force, between anaerobic power and vertical jumping, between anaerobic power and back force, between anaerobic power and leg strength, and between flexibility and vertical jumping. And also, there was a negative and significant relationship between flexibility and agility, between speed and vertical jump, and between agility and vertical jump. In this study, it was concluded that strength, vertical jump and anaerobic power was related both each other and the other. For this reason, we recommend that the trainings cover all motoric characteristics.